Financial openness and macroeconomic volatility - Jürgen von Hagen; Haiping Zhang (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2006)
We analyze the implications of financial openness to macroeconomic volatility in a small open economy. Major macroeconomic aggregates show non-monotonic volatility patterns with respect to the degree of financial openness in the model without domestic financial frictions. The introduction of domestic financial frictions makes the volatility patterns flatter. Our model explains the lack of empirical evidence on the linkage between financial openness and macro volatility. If the empirical data of countries with different degree of financial openness are pooled, we cannot estimate a significant linear relationship between financial openness and macro volatility, because the underlying relationship is non-monotonic.
Keywords: E32; E44; F34; F41; 330; Financial friction; Financial Openess; Foreign borrowing; Macroeconomic volatility